Metaverse Marketing: Avatars as the Future of Brand Engagement - Abdullah Sarwar; Aysa Siddika; Mohammad Ali Tareq; Hayford Asare Obeng; Shaikh Fazlur Rahman; Dzuljastri Abdul Razak (Emerging Science Journal, 2026)
The Metaverse, a virtual space where users interact via avatars, presents a burgeoning platform for marketing endeavors. Unlike traditional social media marketing, which broadcasts to a passive audience, Metaverse marketing facilitates two-way engagement in immersive settings. This is especially relevant for brands aiming to connect with digitally savvy generations, such as Gen X, Millennials, and Gen Z, whose expectations for interactivity and personalization continue to grow. While previous studies have assessed the broader pros and cons of Metaverse marketing, this study examines the avatar as a catalyst for consumer interaction and brand loyalty. The central question was to investigate how avatars influence brand engagement, with a focus on emotional connection and self-expression within the virtual environment. This study explores consumer perceptions, attitudes, and behaviors towards avatars among 398 Malaysian adults. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data. Findings reveal that avatars are effective in enhancing brand recall, trust, and emotional connection. The results also indicate that metaverse brand awareness, customer awareness, trust, and credibility, as well as emotional connection, serve as mediators in the relationship between avatar usage and Metaverse brand engagement. Implications for marketers and future study directions are discussed, highlighting the significance of avatar-based marketing in the evolving digital commerce landscape.